2015
DOI: 10.1093/infdis/jiv762
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Tetravalent Dengue Vaccine Candidate in Healthy Children and Adults in Dengue-Endemic Regions: A Randomized, Placebo-Controlled Phase 2 Study

Abstract: TDV was well tolerated and immunogenic in volunteers aged 1.5-45 years, irrespective of prevaccination dengue exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 25 publications
6
44
0
6
Order By: Relevance
“…Because of the unusual capacity of ZIKV to be transmitted sexually and to cross the placenta, LAVs for ZIKV will be most effective as a childhood vaccine delivered prior to sexual maturity. While the safety profile of many chimeric flaviviruses has been excellent (Kirkpatrick et al, 2016; Sirivichayakul et al, 2016), use of the currently available DENV LAV is limited to those greater than nine years of age (Guy and Jackson, 2016; Hadinegoro et al, 2015). Clinical studies to establish the safety of ZIKV LAVs in an adolescent population will be required.…”
Section: Zikv Vaccine Developmentmentioning
confidence: 99%
“…Because of the unusual capacity of ZIKV to be transmitted sexually and to cross the placenta, LAVs for ZIKV will be most effective as a childhood vaccine delivered prior to sexual maturity. While the safety profile of many chimeric flaviviruses has been excellent (Kirkpatrick et al, 2016; Sirivichayakul et al, 2016), use of the currently available DENV LAV is limited to those greater than nine years of age (Guy and Jackson, 2016; Hadinegoro et al, 2015). Clinical studies to establish the safety of ZIKV LAVs in an adolescent population will be required.…”
Section: Zikv Vaccine Developmentmentioning
confidence: 99%
“…The reactogenicity did not increase with successive vaccination and was not higher in children than in adults and adolescents. Others have also reported of the efficacy of TDV in clinical studies [32][33][34][35][36]. The safety profiles of this vaccine have been evaluated.…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…Although TDV is safe, a number of adverse events have been reported. Sirivichayakal et al [34] reported of the following solicited adverse events (AEs): injection site pain, itching and erythema which was mostly mild while Rupp et al reported of the following unsolicited AEs: headache, fatigue, myalgia and injection site pain [38].…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…Pathogens are also eliminated through herbal agents as well as anti-viral amalgamations are in use against dengue virus. New modified anti-viral agents (against all four serotypes) that are safe, inexpensive but effective at the same time are, however, a growing need [9,37,38].…”
Section: Control and Vaccinationmentioning
confidence: 99%